2018
DOI: 10.3390/ijerph15030481
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis of Epidemiological Investigation of Cancer Risk among People Residing near Nuclear Power Plants in South Korea

Abstract: Background: A 20-year follow-up study on cancer incidence among people living near nuclear power plants in South Korea ended in 2011 with a finding of significantly, but inconsistently, elevated thyroid cancer risk for females. Reanalysis of the original study was carried out to examine the dose–response relationship further, and to investigate any evidence of detection bias. Methods: In addition to replicating the original Cox proportional hazards models, nested case-control analysis was carried out for all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…Although ionizing radiation from the environment has been suggested as a risk factor for thyroid cancer 34 , 35 , we found no significant association between the distance from nuclear power plants and thyroid cancer incidence rate in this study. This finding is contrary to the findings of a previous study that reported women residing within a < 5 km radius from the nuclear power plant as being at high risk of thyroid cancer in Korea 36 . This may be because of the loss of information; the distance from the radiation facility to the center of Sigungu district, rather than the actual distance from each residence to nuclear power plant was used for analyses.…”
Section: Discussioncontrasting
confidence: 99%
“…Although ionizing radiation from the environment has been suggested as a risk factor for thyroid cancer 34 , 35 , we found no significant association between the distance from nuclear power plants and thyroid cancer incidence rate in this study. This finding is contrary to the findings of a previous study that reported women residing within a < 5 km radius from the nuclear power plant as being at high risk of thyroid cancer in Korea 36 . This may be because of the loss of information; the distance from the radiation facility to the center of Sigungu district, rather than the actual distance from each residence to nuclear power plant was used for analyses.…”
Section: Discussioncontrasting
confidence: 99%
“…The impacts of NPPs during operation have been studied in China 10 – 15 and many other countries 16 – 19 . Some of these studies focus on radioactive levels of environmental samples, such as drinking water, food, soil and air, and radiation doses of people living around NPPs, while other studies focus on population health risk and cancer incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies of cancer risks in residents near nuclear power plants (NPPs) have been carried out in at least eleven countries (South Korea, Canada, Finland, France, Germany, Great Britain, Japan, Spain, Sweden, Switzerland, and the United States) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] . The majority of these studies investigated rates of cancer deaths or cancer incidence in residents living in various-distance geographic units, including counties and municipalities.…”
Section: Introductionmentioning
confidence: 99%